Intensive enhanced cognitive behavioural therapy for severe and enduring anorexia nervosa: A longitudinal outcome study. (February 2017) - Calugi, Simona; El Ghoch, Marwan; Dalle Grave, Riccardo
Abstract: Objective: This study aimed to evaluate short- and long-term outcomes in patients with severe and enduring anorexia nervosa (SE-AN), as compared with those with non SE-AN (NSE-AN), both treated via an inpatient programme based on a "recovery model" approach. Methods: Sixty-six adult patients with anorexia nervosa (AN) were recruited from among consecutive referrals to a community-based eating disorder clinic offering inpatient enhanced cognitive behavioural therapy for eating disorders (CBT-E). Body mass index (BMI), and Eating Disorder Examination (EDE) and Brief Symptom Inventory (BSI) scores were recorded at admission, at the end of treatment, and at 6- and 12-month follow-ups. Results: Thirty-two patients (48.5%) were classified as SE-AN (i.e., duration of illness >7 years), and 34 (51.5%) as NSE-AN. During the treatment, both groups displayed similarly large increases in BMI, as well as improvements in eating-disorder and general psychopathology. After discharge minor deterioration did occur, but both NSE-AN and SE-AN groups showed similar rates of 'good BMI outcome' (BM ≥ 18.5; 44.0% and 40.7%, respectively) and 'full response' (BMI ≥ 18.5 and minimal eating-disorder psychopathology; 32.0% and 33.3%, respectively) at 12-month follow-up. Conclusions: These findings suggest that inpatient CBT-E is well accepted by patients with AN, and could also be a viable and promising treatment for those with SE-AN. Highlights: There is no consensus on how to treat severe and enduring anorexia nervosa (SE-AN). Patients with SE-AN and without SE-AN were treated with inpatient CBT-E. At discharge both groups had improvement of body mass index and psychopathology. At 12-month follow-up more than 40% in both groups had a good BMI outcome. Inpatient CBT-E is a viable and promising treatment for patients with SE-AN.